2022
DOI: 10.3390/antibiotics11010065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Novel Anticoccidial Analogue on Systemic Staphylococcus aureus Infection in a Bioluminescent Mouse Model

Abstract: In this study, we investigated the potential of an analogue of robenidine (NCL179) to expand its chemical diversity for the treatment of multidrug-resistant (MDR) bacterial infections. We show that NCL179 exhibits potent bactericidal activity, returning minimum inhibitory concentration/minimum bactericidal concentrations (MICs/MBCs) of 1–2 µg/mL against methicillin-resistant Staphylococcus aureus, MICs/MBCs of 1–2 µg/mL against methicillin-resistant S. pseudintermedius and MICs/MBCs of 2–4 µg/mL against vancom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…NCL265 (MIC range 2–32 μg/mL) demonstrated more potent antimicrobial activity against a variety of Gram-negative human and animal isolates, including human KAPE pathogens compared to NCL259 (8–64 μg/mL), suggesting that the smaller size of these monomeric robenidine analogues may enable penetration of the Gram-negative outer membrane through porins (thus reaching the likely target site within the bacterial inner membrane) compared to the larger dimeric guanidine and pyrimidine-based structures. As we have previously shown, much improved MICs were obtained for both molecules in the presence of outer membrane permeabilizers, a feature of both the parent compound (NCL812) and previously described dimeric analogues NCL195 and NCL179 [ 22 , 23 , 25 , 42 ]. Whilst outer membrane permeabilizers such as EDTA may facilitate transport across the outer membrane through destabilization and loss of lipopolysaccharide chains, outer membrane permeabilizers could also affect microbial efflux systems [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…NCL265 (MIC range 2–32 μg/mL) demonstrated more potent antimicrobial activity against a variety of Gram-negative human and animal isolates, including human KAPE pathogens compared to NCL259 (8–64 μg/mL), suggesting that the smaller size of these monomeric robenidine analogues may enable penetration of the Gram-negative outer membrane through porins (thus reaching the likely target site within the bacterial inner membrane) compared to the larger dimeric guanidine and pyrimidine-based structures. As we have previously shown, much improved MICs were obtained for both molecules in the presence of outer membrane permeabilizers, a feature of both the parent compound (NCL812) and previously described dimeric analogues NCL195 and NCL179 [ 22 , 23 , 25 , 42 ]. Whilst outer membrane permeabilizers such as EDTA may facilitate transport across the outer membrane through destabilization and loss of lipopolysaccharide chains, outer membrane permeabilizers could also affect microbial efflux systems [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 56%
“…Given our previous findings that the combination of NCL812, NCL195, or NCL179 with Gram negative outer membrane permeabilizers (EDTA and polymyxins) could result in a synergistic or additive activity against Gram-negative bacteria [ 22 , 23 , 25 , 42 ], we also tested NCL259 or NCL265 activity in combination with PMB. For the Gram-negative bacteria reference strains tested, either a synergistic or additive interaction was observed, reducing the MIC of NCL259 by 8- to 256-fold and the MIC of NCL265 by 4- to 256-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice that received two intraperitoneal doses of 50 mg/kg NCL195 exhibited significantly reduced S. aureus loads compared to untreated mice, but still succumbed to infection (28). Interestingly, we recently showed that mice treated with four 50 mg/kg oral doses of a closely-related robenidine analogue (NCL179) had significant increase in overall survival rate after S. aureus challenge compared to the vehicleonly control (30). This provided the opportunity to investigate the efficacy of oral NCL195 and intraperitoneal colistin combination as a proof of concept of in vivo antimicrobial activity against GNB in a bioluminescent mouse peritonitis-sepsis model.…”
Section: Introductionmentioning
confidence: 99%